2022
DOI: 10.1021/acs.jpcc.2c00227
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Computational Screening of in Silico Designed MOFs for Efficient SO2 Capture

Abstract: SO 2 presence in the atmosphere can cause significant harm to the human and environment through acid rain and/or smog formation. Combining the operational advantages of adsorption-based separation and diverse nature of metal–organic frameworks (MOFs), cost-effective separation processes for SO 2 emissions can be developed. Herein, a large database of hypothetical MOFs composed of >300,000 materials is screened for SO 2 /CH 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…These computational approaches to incorporate flexibility have shown that framework motion can have strong effects on guest molecule properties, 19,34–38 such as adsorption 39–41 and diffusivity, 25,27,42–48,57 in accordance with experiment. 20,47,58–65 Yang et al 47 studied the diffusion of methane in UiO-66 using flexible force fields and observed a significant improvement in prediction over rigid force fields, although predictions were still lacking in quantitative and qualitative agreement with experiment.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…These computational approaches to incorporate flexibility have shown that framework motion can have strong effects on guest molecule properties, 19,34–38 such as adsorption 39–41 and diffusivity, 25,27,42–48,57 in accordance with experiment. 20,47,58–65 Yang et al 47 studied the diffusion of methane in UiO-66 using flexible force fields and observed a significant improvement in prediction over rigid force fields, although predictions were still lacking in quantitative and qualitative agreement with experiment.…”
Section: Introductionmentioning
confidence: 59%
“…This approach allows for a less computationally demanding means of accessing the variation in channel environment, but it relies on the assumption that the presence of guest molecules has a negligible impact on the dynamic configurations of the MOF, which does not hold true for all MOFs. 26,27 These computational approaches to incorporate flexibility have shown that framework motion can have strong effects on guest molecule properties, 19,[34][35][36][37][38] such as adsorption [39][40][41] and diffusivity, 25,27,[42][43][44][45][46][47][48]57 in accordance with experiment. 20,47,[58][59][60][61][62][63][64][65] Yang et al 47 studied the diffusion of methane in UiO-66 using flexible force fields and observed a significant improvement in prediction over rigid force fields, although predictions were still lacking in quantitative and qualitative agreement with experiment.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Due to the time and cost limitations, it is impossible to carry out a large‐scale exploration through trial‐and‐error experiments 35,36 . In this context, high‐throughput computational screening can be handily performed to guide the experimentalists toward the right direction by predicting the performance of a large library of structures thanks to the development of computational resources and algorithms 37–39 …”
Section: Introductionmentioning
confidence: 99%
“…35,36 In this context, high-throughput computational screening can be handily performed to guide the experimentalists toward the right direction by predicting the performance of a large library of structures thanks to the development of computational resources and algorithms. [37][38][39] Herein, we performed high-throughput grand canonical Monte Carlo (GCMC) simulations to predict the SO 2 /CO 2 separation performance in an anion-pillared MOF database through using our in-house code, namely high-throughput-based complex adsorption and diffusion simulation suite (HT-CADSS). 40 The relationship between SO 2 / CO 2 separation performances and structural characteristics was established based on the simulation results.…”
mentioning
confidence: 99%